Korelasi Genetik Pada Sifat Pertumbuhan Sapi Aceh di Kecamatan Indrapuri Provinsi Aceh - Widya Pintaka Bayu Putra; Sumadi Sumadi; Tety Hartatik (Agricultural Faculty, 2014)
(The genetic correlation of growth traits in Aceh cattle at indrapuri district Aceh Province)ABSTRACT. This research was conducted to estimate genetic correlation of growth traits on Aceh cattle including birth weight (BW), weaning weight (WW), yearling weight (YW), and Average Daily Gain (ADG). The research was done at Indrapuri Breeding and Forage Centre (IBFC) of Aceh cattle from March 2013 to April 2013. The materials of this research consist of growth records from 2010 to 2012. The genetic correlation was analyzed by variance and covariance. The results indicated that the lowest standard error (SE) value of heritability showed on birth weight 0.15+0.13. Most of genetic correlation value on growth traits was positive and high categorized ( 0.50). The lowest SE value showed on correlation between birth weight and pre-weaning ADG (0.55+0.54), birth weight and post-weaning ADG (0,63+0,62), pre-weaning ADG and post-weaning ADG (0.71+0.33), pos-weaning ADG and weight/age or W/A (0.72+0.33) then final weight and W/A (0.94+0.69). It could be concluded that most of genetic correlation value on Aceh cattle growth traits were positive and high therefore the selection based on growth traits can be done for increasing performance in Aceh cattle.